Cybersecurity risks of GIS technology for smart communities. A case study - Galassi, Alessandra (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
Digital Transformation (DT) is changing the city-citizen relationship, pushing to rethink urban development models to make them consistent with new socio-economic needs, particularly related to land livability and social inclusion. This article aims to provide an overview of digital security issues related to Geographical Information Systems (GIS) useful for rethinking cities in smart terms. In this specific case, a special Public Administration (PA) called the Special Office for the Reconstruction of the Municipalities of the Seismic Crater (USRC) adopts GIS as a tool to support its efforts in post-earthquake reconstruction by creating attractive smart communities. Briefly, the objective is to explore the cybersecurity aspects of GIS and how these should be considered as part of risk management, vulnerabilities of GIS related to information security, and suggest recommendations. The synergy of GIS with other technologies is also discussed, reflecting how technological innovation has pros and cons for an organization.